Análisis técnico económico de la futura línea de transmisión Coca Codo Sinclair-Pifo a 500KV - Jaramillo Segarra, Diego Andrés (2011)
Demand grows in Ecuador between 5% and 7% per year, to cover this growth need new generation projects and new transmission projects. The bigger project in Ecuador will be the Coca Codo Sinclair with 1500 MW of power, this ability will be transmitted to the big load center that is Quito by the transmission line to 500 KV Coca Codo Sinclair - El Inga (Pifo), to this lines is going to connect with transmission lines El Inga (Pifo) - Yaguachi - Sopladora, to join the project Sopladora. However in the world there are other levels of EHV as 345 KV and 750 KV, which can be used, that is the reason why made a technical - economic comparison of these levels of voltage with the proposed project of 500 KV, to determine the appropriate option. Using a power flow study in the year 2016 have been obtained values of power losses in transmission lines Coca Codo Sinclair - The Inga (Pifo) and the whole system of transmission lines proposed, using data on other systems EHV employees worldwide. Of the three voltage levels tested, the inversion in the alternative to 345 KV is less, however the power and energy losses are greater in this alternative, so the economic losses are also higher than the other two systems of voltage. In this study reached to determine the most optimal system voltage in transmission lines Coca Codo Sinclair - The Inga (Pifo) - Yaguachi - Sopladora is the alternative to 345 KV, with a cable ACAR 1250. In this alternative, the Liquid Present Value is greater than the project to 500 KV and 750 KV alternative, so this project is more feasible for implementation in Ecuador.